Use of skimmed breast milk for an infant with a long‐chain fatty acid oxidation disorder: A novel therapeutic intervention. Issue 1 (30th July 2020) - Kritzer, Amy; Tarrant, Stacey; Sussman‐Karten, Karen; Barbas, Kimberly
Abstract: The focus of dietary therapy for long chain fatty acid oxidation disorders (LC‐FAODs) is to minimize fatty acid oxidation by avoiding fasting and providing sufficient calories. Dietary therapy involves restriction of long‐chain triglycerides (LCT), and provision of medium‐chain triglycerides as an alternate energy source. It is well established that the use of breast milk through the first year of a newborn's life has significant health benefits. While very few medical contraindications to breastfeeding exist, feeding an infant with a severe carnitine acylcarnitine translocase (CACT) deficiency typically requires cessation of breastfeeding as approximately 50% of the calories in human milk come from LCT. In this case report, we present the innovative and successful use of skimmed breast milk incorporated into the dietary management of an infant with severe CACT deficiency. Given the poor prognosis for individuals with severe CACT deficiency on standard dietary therapy, the use of skimmed breast milk represents an important measure to try to improve short‐term and long‐term outcomes. Given the many proven benefits of breast milk, this case illustrates that skimmed breast milk can be combined with appropriate fat sources to provide complete nutrition for children with severe CACT deficiency. After over 12 months on this regimen, this patient has experienced normal growth and development and has had no acute decompensations.